(untitled) (Research, Society and Development, 2020)
The quality of the seedlings used in planting is fundamental to the success of a papaya orchard. The objective of this work was to evaluate different substrates with green manure composts and foliar fertilization with biofertilizer ’supermagro’ on the growth and nutrient accumulation in seedlings of papaya ’Formosa’ and papaya ’Golden’. The substrates used were: soil (S), soil + cattle manure (S+M), soil + cattle manure composted with black oats straw (S+AS), soil + cattle manure composted with ryegrass straw (S+RS), soil + cattle manure composted with turnip straw (S+TS), and soil + cattle manure composted with vetch straw (S+VS). Substrates containing cattle manure or green manure composts improving the development of papaya seedlings. The best results for the development of papaya ’Golden’ seedlings were found on the substrates containing S+M, S+AS and S+VS. Papaya ’Formosa’ seedlings grown on the substrate with S+CEV showed increased P, Ca and Mg accumulation in dry matter. However, papaya ’Golden’ seedlings had higher N and P accumulation in dry matter when grown on substrate containing S+E and increased Ca accumulation on substrate with S+CEV. Foliar application of biofertilizer in papaya ’Formosa’ seedlings decreased the N and Ca accumulation but increased the P accumulation and root length and volume, while dry matter production was not affected. Nonetheless, in papaya ’Golden’ seedlings the foliar biofertilizer application increased root volume but reduced total and shoot dry matter and N, P, K accumulation.